(untitled) (American Journal of Islam and Society, 2004)
Davis seeks to present a balanced view of terrorism vs. martyrdom, moderate vs. radical, the Muslim world vs. the West, and why 9/11 happened. The author is deputy foreign editor at Knight Ridder newspapers and is a regular contributor to her company’s 32 newspapers. In chapter 1, “A Minister’s Question,” Davis, an African-American practicing Christian, wonders why African-Americans mainly have chosen non-violence, while the self-professed Muslims held responsible for 9/11 chose violence. As both groups ground their struggle for justice in their respective religions, this gives rise to a paradox: Can God provide “superior” and “inferior” revelations? Muslims are told to “fight injustice” (e.g., 8:39, 22:39), while Christians are called upon to “turn the other cheek” (Matthew 5:39). Matthew 10:34-37, about Jesus “bringing a sword” is also instructive. Moreover, if “Jesus Christ [is] the same yesterday, and today, and forever” (Hebrews 13:8) and Jesus is God, what is one to make of the Old Testament’s record of divinely sanctioned slaughter? She defines martyr according to the religion’s general view (Christianity: “generally a pacifist who suffers and dies but not kill” [p. 8]; Islam: “everyone who dies in the midst of battle defending his homeland or fighting evil” [p. 9]), but does not define militant, extremist, terrorist, or moderate – a curious omission, since there are no agreed-upon meanings for them. Chapter 2, “The Innocents,” discusses the deaths of Palestinian and Israeli children, how both sides exploit their martyrs (“anyone who dies in the midst of battle” [p. 27]), and mutual charges of deliberate child endangerment. She interviews parents and surviving siblings, and states that this has become a vicious circle of revenge, and relates the various psychological impacts as charges of western indifference to Palestinian deaths, and Israel’s continued defiance of UN resolutions. Chapter 3, “The Child as Soldier-Martyr,” opens with her visit to Iran’s Martyrs Museum. She wonders if Iran might turn this “ultimate” weapon on itself as “stridently” conservative mullahs and the “freedom-hungry and angry” youths move closer to violence. After explaining Shi’ism’s origins and key events, she mentions the martyrdom of a 12-year-old boy who ...